(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article discusses the importance of pronunciation in foreign language teaching. With the help of this article, the author tried to teach his students the importance of a foreign language, to create a German environment in the classroom, to pronounce and speak in the organization of the lesson. The factors mentioned in the article will undoubtedly create a sense of pride and pride in the Motherland among cadets and officers.